2008
DOI: 10.1007/s10551-008-9824-y
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ethical Perceptions of Managers and Non-Managers

Abstract: deontological views, ethical perceptions, income, managers, nature of organizations, non-managers, professionals,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
(32 reference statements)
3
29
1
Order By: Relevance
“…Fourth, the scale reliabilities were in some cases low. Although, it has been suggested that statistical analysis alphas above 0.6 (Ge and Thomas 2008;Murphy and Davidshofer 1998;Robinson et al 1991) or above 0.5 (Park et al 2008;Siu and Lam 2009) may be considered reasonable and adequate (see also Cronbach 1951), our findings need to be interpreted with caution as the Cronbach a of three scales used in this study is below the commonly recommended alpha of 0.7 (Nunnally 1978). Fifth, we have only investigated the use of external and anonymous whistleblowing and have not included reverse-coded items for internal and identified whistleblowing.…”
Section: Discussionmentioning
confidence: 53%
“…Fourth, the scale reliabilities were in some cases low. Although, it has been suggested that statistical analysis alphas above 0.6 (Ge and Thomas 2008;Murphy and Davidshofer 1998;Robinson et al 1991) or above 0.5 (Park et al 2008;Siu and Lam 2009) may be considered reasonable and adequate (see also Cronbach 1951), our findings need to be interpreted with caution as the Cronbach a of three scales used in this study is below the commonly recommended alpha of 0.7 (Nunnally 1978). Fifth, we have only investigated the use of external and anonymous whistleblowing and have not included reverse-coded items for internal and identified whistleblowing.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, Siu and Lam (2009) compared ethical perceptions of managers and non-managers in Hong Kong, and found that managers tend to adhere to higher ethics standards, than non-managerial employees. According to the National Business Ethics Survey, conducted by ECR, 'the more senior an employee is, the more useful he is apt to find ethics training' (Training 2005, 15).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Although we did not find studies contrasting directly the care/justice preferences of managers and non-managers, we found evidence suggesting that managers value fairness more (a key component of ethics of justice) and are more rule-driven than non-managers (Siu and Lam 2009). Brown and Treviño's (2006) literature review describes ethical leaders as ''fair and principled decision-makers'' (p. 597).…”
Section: On Managerial Statusmentioning
confidence: 54%